Providing a structural model of psychological well-being prediction based on family functioning, optimism, and resilience mediated by social adequacy - Lotfnejadafshar, Sima; Khakpour, Reza; Dokanehi Fard, Farideh (Applied Family Therapy Journal (AFTJ), 2022)
Aim: This study was conducted to provide a structural model of psychological well-being prediction based on family functioning, optimism, and resilience mediated by social adequacy. Methods: This was a descriptive correlational study with structural equation modeling (SEM). The statistical population included students of Allameh Tabatabaei Campus in Urmia (for sisters) and Shahid Rajaei Campus in Urmia (for brothers) from which 250 people were selected as the sample by convenient sampling method. The study tools were Ryff’s (1989) Psychological Well-Being Scales (PWB), McMaster’s (1950) Family Assessment Device (FAD), Scheier and Carver’s (1985) Life Orientation Test (LOT), Connor-Davidson (2003) Resilience scale (CD-RISC), and Flanner et al.’s (1990) Social Adequacy Scale. Results: The findings suggested that there was a positive relationship between resilience and psychological well-being (p <0.01, β = 0.240). The total path coefficient between optimism and psychological well-being was positive and significant at the level of 0.01 (p <0.01, β = 0.317). Besides, the total path coefficient between family functioning and psychological well-being was negative (p <0.01, β = -0.225). The path coefficient between social adequacy and psychological well-being was positive and significant at the level of 0.01 (p <0.01, β = 0.225). Indirect path coefficient between resilience (p <0.01, β = 0.089), optimism (p <0.01, β = 0.094), and psychological well-being was positive, and indirect path coefficient between family functioning and psychological well-being (p <0.01, β = -0.101) was negative and significant at the level of 0.01. Conclusion: According to the results, resilience and optimism predicted psychological well-being positively and significantly, family functioning predicted psychological well-being negatively and significantly, and social adequacy mediated the relationship between resilience and optimism positively and significantly and the relationship between family functioning and psychological well-being positively and significantly.